Enhancing public private partnership for effective infrastructural development of lokoja town - Yusufu, Ojochenemi Sunday; Alabi, Olatunji John; Idachaba, Odekina Innocent (2020)
Public-Private Partnership (PPP) have been identified as one of the viable means to effectively address infrastructural deficit and maintenance of public structure. This study explores public private partnership as an effective means to infrastructural development of lokoja town. The study adopted survey method which involves the administration of structured questionnaire to collect primary data from respondents. The population of the study consist of the entire population of lokoja which stood at 195261 according to the 2006 census figure. To determine the sample size, the study adopted smith (1984) formula to arrive at a sample size of 397. Based on this, 397 questionnaire were distributed to respondents to elicit their view. 300 questionnaire were returned. The study made use of descriptive statistic and multiple linear regression analysis to test the hypothesis and analyze the data collected. Findings reveals that risk management is significant on infrastructural development based on the regression result (Beta =.409 ;P=0.000 < 0.05). The study also found that managerial expertise is significant on infrastructural development based on the regression result (Beta =.552 ;P=0.000 < 0.05). The study concludes that collaboration through public private partnership enhances infrastructural development and better standard of living in the area of social amenities. The study recommended that public private partnership should constitute stakeholders of high integrity to mitigate high risk factor in terms of Infrastructure Procurement . Also, the study recommends that quality project execution should be adhered to by all parties involved.